THE JĀTAKAMĀLĀ RELIEFS OF BOROBUDUR: BENEFICIAL AND INSIGHTFUL ACTS IN ADVERSE TIMES - LEE, So Tju Shinta (International Review of Humanities Studies, 2021)
This study is aimed to examine seven selected allegories of Āryaśūra’s Jātakamālā engraved in Candi Borobudur, to analyze the multiple aspects of the six perfections (pāramitās) exemplified in them and how these perfections are applied in day-to-day life. The literature study involved data collection triangulation to determine the extant Jātakamālā and pāramitā texts closest to the sources. Content analysis on the Jātakamālā texts and observation of its corresponding reliefs were carried out to identify the message and substantial points of each allegory. Both the actions and the motivation driving the character to perform such actions are considered. Using thematic analysis, the actions performed are categorized and correlated with the definition and meaning of each pāramitā. The results of the research indicate that although emphasis may be placed more on a particular perfection, multiple aspects of the perfections are presented in each allegory. The practice of the six perfections which to be cultivated jointly by those walking the path to Perfect Awakening also represent the universal values of generosity, non-harmfulness, tolerance, joyous effort, vigilance, and wisdom. This study allows one to see Borobudur’s carved reliefs in a way, which will hopefully engender appreciation for the cultural heritages of our ancestors.